Curcumin attenuates delayed-onset muscle soreness and muscle function deficits following a soccer match in male professional soccer players - Abbott, W.; Hansell, E. J.; Brett, A.; Škarabot, J.; James, L. J.; Clifford, T. (International Journal of Sports Physiology and Performance, 2023)
To examine the effects of acute curcumin (CURC) supplementation on recovery from a soccer match in male professional players. Methods: In a randomized, placebo-controlled, crossover design, 11 players from the under-23 team of an English Premier League club (age 19 [1] y, body mass 79.4 [7.9] kg, height 180.8 [5.7] cm) consumed 500 mg of CURC or a control (medium-chain triglycerides) immediately and 12 and 36 hours after a 90-minute match. Countermovement jump height (CMJ), reactive strength index (RSI), delayed-onset muscle soreness (DOMS, 0-200 mm), and subjective well-being were measured before and 12, 36, and 60 hours postmatch. Global positioning systems measured external load during matches, and dietary intake was recorded across the testing period. Results: External load and dietary intake did not differ between conditions (P = .246). CURC attenuated deficits in CMJ (P = .004) and RSI (P = .001) and reduced DOMS (P = .004) at all postmatch time points (except 60 h post for RSI). The greatest difference between control and CURC was 12 hours post for CMJ (P < .001, 1.91 [4.40] cm, 95% CI, 1.25 to 2.57, g = 0.36) and RSI (P = .003, 0.40 [0.41] AU, 95% CI, 0.17 to 0.63, g = 0.90) and 36 hours post for DOMS (P < .001, 47 [23] mm, 95% CI, -67 to -27, g = 2.12). Conclusions: CURC intake <36 hours after a soccer match attenuated DOMS and muscle function deficits, suggesting that CURC may aid recovery in professional male soccer players.